Short-interval intracortical inhibition (SICI): effect of target tracking on variability of responses for 1 mV and 200µV test-alone targets - Fanella, Gaia; Bostock, Hugh; Samusyte, Gintaute; Jacobsen, Anna Bystrup; Howells, James; Cengiz, Bülent; Kılınç, Hasan; Koltzenburg, Martin; Abrahao, Agessandro; Zinman, Lorne; Bardel, Benjamin; Lefaucheur, Jean-Pascal; et al. (Neurophysiologie clinique, 2025)
To evaluate whether continuously tracking unconditioned thresholds for maintaining constant motor-evoked potential (MEP) amplitudes improves the variability of amplitude-based short-interval intracortical inhibition (SICI) measurements. Fifty-five healthy subjects were tested twice on two days with six SICI protocols. Conditioning stimulus (CS) intensity was set to 70 % of the resting motor threshold for a 200µV target (RMT200), while test stimulus (TS) intensity targeted MEP of either 1 mV or 200µV. Protocols included conventional A-SICI (fixed CS and TS), hybrid A-SICI (fixed CS and updated TS by threshold tracking); tracked A-SICI (both CS and TS updated by threshold tracking). Variability in unconditioned and conditioned responses was analyzed across interstimulus intervals (ISIs) of 1, 2.5, and 3 ms. Threshold-tracking reduced variability of the unconditioned responses measured by geometric standard deviation (expressed as a factor) for 1 mV (×/÷1.61 to 1.39; p<0.0001) and 200µV targets (×/÷2.21 to 1.30; p<0.0001). However, variability of inhibition measures did not differ significantly across protocols. Inhibition with the 200µV MEP target was significantly less than with 1 mV across all ISIs (p<0.001). The A-SICI 200µV tracked protocol showed reliability comparable to A-SICI fixed 1 mV, suggesting it may be a practical alternative in clinical populations where achieving a 1 mV MEP is challenging, such as in patients with severe muscle denervation. While threshold-tracking enhances unconditioned MEP reproducibility, it does not reduce the variability of SICI, which is highly dependent on target MEP size. These findings point towards two distinct mechanisms underlying conditioned and unconditioned responses and refine understanding of SICI variability.